Code Switching in the Toba Batak Wedding Ceremony - Rakhmat Wahyudin Sagala; Lince Sihombing; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2014)
The aims are to find out: 1) the types of code switching used in the Toba Batak wedding ceremony, 2) how the participants switch language in the process of Toba Batak wedding ceremony, and 3) reason why the participants switch language in the process of Toba Batak wedding ceremony. The data were obtained from the utterances of participants which contain code switching during the process of Toba Batak wedding ceremony precisely in Marhaban, replying and exchanging the verses of rhymes, exchanging of Tepak, and upah-upah stages. They were analyzed by using some steps as normally applied in descriptive qualitative method. The instruments of data collection were audio visual recorder. The findings of the study indicate that; a) Three types of code switching found namely intrasentential, intersentential and tag switching b) Participants in Toba Batak wedding ceremony mix some languages based on participants’ tribes which involved in the process of Toba Batak wedding ceremony and they also adjust the situation and the condition of the people c) Three reasons of code switching during the process of Toba Batak wedding ceremony namely the differences of family’s tribes, religion factor and place of wedding ceremony be held. Keywords: Code Switching; Toba Batak; Traditional Marriage